EFFECTS OF DEMOGRAPHIC VARIABLES ON CONSUMER BUYING BEHAVIOUR TOWARD FROZEN FOODS - Ishfaque Ahmed, Ali Akbar Pirzado, Arman Khan, Abdul Rauf Laghari, Rashid Ali Chandio, Saleem Zardari, Komal Aarain (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Frozen foods are also known as convenience food. As there is change in the socioeconomic conditions of Pakistan so the demand of frozen food also increases. This would be the emerging market in Pakistan. It is still in its initial stage in Pakistan but this industry matures in developed countries. The main reason about the increase in use of frozen meals is because there is change in work force and more women are participating in work force and food buying decision are generally taken by women. Frozen foods are generally used by many women who are not working because they use it as snacks for kids and for the guests. Variables such as price, income, culture, taste, family size and brand association has great influence on buying behavior of consumer of ready to eat frozen food. The methodology used in this study is descriptive approach. Simple random sampling technique was used for collection of data. There are too many opportunities in the frozen food industry. Many varieties of products can be offered in this category. The continuous improvement and product development and awareness of frozen food can helps the local producer to compete with international brands.